Pengaruh Teknologi E-Commerce terhadap Peningkatan Penjualan - Nadia Syahrani (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
This research aims to analyze the effect of using e-commerce technology on increasing sales in companies that have adopted e-commerce platforms as their sales channels. The research approach used is descriptive research with quantitative analysis, which involves collecting data through direct observation and case studies on 5 companies in Indonesia that actively use e-commerce. The research results show that the application of e-commerce technology has a positive effect on increasing sales volume, operational efficiency and expanding market reach. E-commerce makes it easy for companies to access consumers from various locations, increasing shopping convenience and smooth transaction processes. However, the main challenge found was the issue of consumer trust in the security of online transactions and the protection of personal data. This research concludes that e-commerce technology has great potential to increase company sales, with companies needing to address security issues to improve